2017
DOI: 10.18632/oncotarget.17612
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ZnO nanoparticles alters intestinal microbiota and inflammation response in weaned piglets

Abstract: The present study was carried out to determine whether low dose of zinc oxide nanoparticles (Nano-ZnO) could serve as a potential substitute of pharmacological dose of traditional ZnO in weaned piglets. 180 crossbred weaning piglets were randomly assigned to 3 treatments. Experimental animals were fed basal diet supplemented with 0 mg Zn/kg (Control), 600 mg Zn/kg (Nano-ZnO) and 2000 mg Zn/kg (ZnO) for 14 days. On day 14 after weaning, the piglets fed Nano-ZnO did not differ from those fed traditional ZnO in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 39 publications
6
79
0
Order By: Relevance
“…It has been reported that pharmacological does of ZnO can increase villus height and reduce crypt depth in the small intestine of weaned piglets (Li et al 2001). Furthermore, Xia et al (2017) demonstrated that low dose of zinc oxide nanoparticles had comparable effects on improving jejunal morphology to a high dose of traditional ZnO. In the present study, supplementation with low does C-ZnO, as well as high does ZnO, had higher villus height at the jejunal mucosa as compared with the control.…”
Section: Discussionsupporting
confidence: 59%
“…It has been reported that pharmacological does of ZnO can increase villus height and reduce crypt depth in the small intestine of weaned piglets (Li et al 2001). Furthermore, Xia et al (2017) demonstrated that low dose of zinc oxide nanoparticles had comparable effects on improving jejunal morphology to a high dose of traditional ZnO. In the present study, supplementation with low does C-ZnO, as well as high does ZnO, had higher villus height at the jejunal mucosa as compared with the control.…”
Section: Discussionsupporting
confidence: 59%
“…Notably, three ingredients (dried whey, fish meal and zinc oxide) were included in Phase II diets, but not in Phase III diets ( Supplementary File 1). As its primary use is to prevent diarrhea, zinc oxide represents a likely candidate modulator of gut microbiome composition [46][47][48][49][50]. However, its target bacterial groups in gut environments remain to be further investigated, as exemplified by two conflicting studies, one observing a decrease in Lactobacilli as a result of dietary inclusion of zinc oxide [48], while the other reported no effect [51].…”
Section: Bacterial Succession From Lactobacillaceae In Phase II To Stmentioning
confidence: 99%
“…Supplementation of zinc can increase bacterial diversity, richness, and activity in the ileum of piglets [ 76 , 77 , 78 ]. Moreover, zinc deficiency may promote the development of T1D via affecting the inflammatory response and impacting the metabolic control [ 79 ]. In addition, prebiotics via food additives elevate protective intestinal microbiota and improve the permeability of the intestinal barrier, thus helping to improve health and prevent the development of diet-related chronic diseases including diabetes [ 80 , 81 ].…”
Section: Diet Gut Microbiota and T1dmentioning
confidence: 99%